Outsourcing Strategies and Organizational Performance in Nigerian Banking Industry - Iyamabhor Martins; Ekpeni Ogechukwu Perpetual (CV. Proaksara Global Transeduka, 2025)
The research is centred on how outsourcing strategies impact the performance of organisations. The main goals of the research are to investigate how outsourcing payroll services affects organisational performance and to explore how outsourcing mystery shopping services impacts organisational performance. The study utilised descriptive survey research methods and the study population consisted of employees from selected banks in Asaba - specifically, first bank and access bank, totalling 400. The sample size was determined using the Taro Yamani formula, resulting in a sample of two hundred (200). The respondents were chosen using a method called stratified sampling. The results showed that when companies outsource their payroll and mystery shopping services, it positively impacts their overall performance. It was found that the success of outsourcing agreements greatly depends on how outsourcing vendors are selected. It is important to carefully assess the criteria used to evaluate potential vendors to ensure the best performance. The research suggests that banks could improve their human resources (HR) operations by outsourcing to gain access to expertise and quality services from external providers.